Measurement of bonding strength of thermally reduced graphene oxide with soda lime glass using nanoscratch technique. (2018) - Kumar, Raj; Kumar, R. Manoj; Lahiri, Debrupa; Lahiri, Indranil
Abstract: In this study, soda lime glass was reported to use as transparent conducting electrode. Soda lime glass was made conducting with graphene film deposited through simple, low cost, scalable and easy to operate thin film deposition technique. Graphene oxide was dip-coated on soda lime glass, followed by reduction into rGO by thermal annealing in two different atmospheres Ar and Ar+H2 at 500 °C. Bonding strength of GO and rGO (Ar and Ar+H2 treated) with soda lime glass were measured through nanoscratch technique to understand the adhesion behavior of film with substrate. There was no significant effect of reduction atmosphere found on transmittance of the films. However, films, reduced in Ar+H2 atmosphere, showed the low sheet resistance than reduced in Ar only. Highest transmittance of 97.98% and lowest sheet resistance of 12.5×10 3 Ω/sq were calculated under different processing conditions.